MEMBANGUN KARAKTER ANAK MELALUI OLAHRAGA TRADISIONAL: PERSPEKTIF FILSAFAT PENDIDIKAN DI SEKOLAH DASAR - Rudy Juli Saputra; Arie Rakhmat Riyadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article aims to analyze the role of traditional sports as a medium for character formation in elementary school children from the perspective of educational philosophy. The focus of the study is directed at the relationship between physical activity, local wisdom, playing experience, and the internalization of character values. This research uses a qualitative approach with a literature study design and conceptual-philosophical analysis. Data were obtained from journal articles, educational theory books, curriculum documents, and policy sources relevant to physical education, traditional sports, ethnopedagogy, and character education. The analysis was carried out through the stages of source reduction, thematic coding, value categorization, and philosophical synthesis. The results of the study indicate that traditional sports have pedagogical power because they unite the dimensions of body, feeling, reason, sociality, and culture. The literature synthesis revealed five dominant themes, namely character formation (35.0%), local wisdom and culture (22.5%), participation and motor skills (17.5%), pedagogical models (15.0%), and curriculum support (10.0%). The most prominent character values ​​include cooperation/mutual assistance (22.5%), discipline (17.5%), honesty/sportsmanship (15.0%), responsibility (15.0%), self-confidence (12.5%), tolerance (10.0%), and social concern (7.5%). This article offers the ACTIVE CULTURE conceptual model as a framework for learning traditional sports based on experience, reflection, value dialogue, and character assessment